2001
DOI: 10.1590/s1415-47572001000100015
|View full text |Cite
|
Sign up to set email alerts
|

In silico differential display of defense-related expressed sequence tags from sugarcane tissues infected with diazotrophic endophytes

Abstract: The expression patterns of 277 sugarcane expressed sequence tags (EST)-contigs encoding putative defense-related (DR) proteins were evaluated using the Sugarcane EST database. The DR proteins evaluated included chitinases, β-1,3-glucanases, phenylalanine ammonia-lyases, chalcone synthases, chalcone isomerases, isoflavone reductases, hydroxyproline-rich glycoproteins, proline-rich glycoproteins, peroxidases, catalases, superoxide dismutases, WRKY-like transcription factors and proteins involved in cell death co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…EST-contigs, expressed in non-stressed organs compared to the stressed organs, were calculated as described in Lambais (2001). Graphical representation of each data was highlighted with a color, using a color scale representing the range between suppression and induction gene expression, in relation to the counterpart control library.…”
Section: Identification and In Silico Expression Analysis Of Citrus Pmentioning
confidence: 99%
See 1 more Smart Citation
“…EST-contigs, expressed in non-stressed organs compared to the stressed organs, were calculated as described in Lambais (2001). Graphical representation of each data was highlighted with a color, using a color scale representing the range between suppression and induction gene expression, in relation to the counterpart control library.…”
Section: Identification and In Silico Expression Analysis Of Citrus Pmentioning
confidence: 99%
“…A natural basis for organizing gene expression data is to group together genes with similar pat-terns of expression (Eisen et al, 1998). In plants, hierarchical clustering has been used routinely to identify genes highly expressed from rice (Ewing et al, 1999), sugarcane (Lambais, 2001), soybean (Shoemaker et al, 2002), barley (Zhang et al, 2002), wheat (Ogihara et al, 2003) and eucalypt (Domingues et al, 2005) transcriptome; and it is expected that this number will continue to increase. A combination of clustering methods with a graphical representation of the primary data, by representing each data point with a color, may quantitatively and qualitatively reflect the original experimental observations and allow an understanding of the data in a naturally intuitive manner (Eisen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The expression analysis used the so-called 'digital northern blot' (Carraro et al, 2001;Lambais, 2001) to represent the expression profile of the potential homeobox genes and to identify differential expression among the diverse Eucalyptus tissues/treatments used in the FORESTs project. In this approach, the frequency of reads for each EST-contig in each selected library is computed and then normalized with respect to the number of reads in the library and to the total number of reads in all libraries.…”
Section: Phylogenetic and Expression Analysesmentioning
confidence: 99%
“…Since identification of the first WRKY gene SPF1 from sweet potato (Ishiguro and Nakamura 1994), numerous WRKY genes have been identified in different plants, including parsley (Rushton et al 1996), tobacco (Hara et al 2000), sugarcane (Lambais 2001), Arabidopsis thaliana (Chen and Chen 2002), barley (Sun et al 2003), pepper (Oh et al 2006), rice (Liu et al 2007), tomato (Hofmann et al 2008), canola (Yang et al 2009), and grapevines (Marchive et al , 2013Mzid et al 2007;Guillaumie et al 2010;Liu et al 2011;Merz et al 2014). It is reported that WRKY genes have multiple functions in physiological and biochemical processes such as seed germination (Jiang and Yu 2009), root development , dormancy (Rohde and Bhalerao 2007), senescence (Ülker et al 2007), oxidative stress (Miller et al 2008), biotic stresses (Zhu et al 2012;Dang et al 2013;Guo et al 2014;Merz et al 2014), abiotic stresses (Ricachenevsky et al 2010;Rabara et al 2013;Scarpeci et al 2013;Şahin-Çevik et al 2013;Guo et al 2014), and signaling pathways of phytohormones (Li et al 2004;Rabara et al 2013;Guo et al 2014).…”
Section: Introductionmentioning
confidence: 99%